EXTRA-CURRICULAR IMPLEMENTATION OF THE YOUNG MOSQUE ACTIVIST ASSOCIATION IN IMPROVING THE GOOD CHARACTER AND RELIGIOUS DEVOTION AT STUDENTS OF SMPN 6 MAKASSAR - Irawan, Marina Masdayanti; Malli, Rusli; Palangkey, Rahmi Dewanti (Universitas Islam Negeri Alauddin Makassar, 2024)
The aim of this research is to describe the objectives of the extracurricular activities of the PAI Mosque Youth Association at SMPN 6 Makassar. Describe the implementation of PAI Mosque Youth Association extracurricular activities at SMPN 6 Makassar. Describe the supporting and inhibiting factors for extracurricular activities of the PAI Mosque Youth Association at SMPN 6 Makassar. This type of research is field research by taking data sources in the field through interviews as the main source. Supporting data is relevant to the research object that being studied. Then presented several findings regarding the extracurricular activities of the PAI Mosque Youth Association of SMPN 6 Makassar, how the implementation of extracurricular activities of the PAI Mosque Youth Association at SMPN 6 Makassar improving the good character and religious devotion. Inhibiting and supporting factors for the PAI Mosque Youth Association extracurricular program at SMPN 6 Makassar. The results of this research are the extracurricular activities of the PAI Mosque Youth Association in improving the good character and religious devotion. Achieve a balance between physical and spiritual education. During the activity. Starting with an opening, then delivering the material and ending with a closing. Many things are taught such as discipline, responsibility, family in the organization, and leadership. 3) Strategies in the extracurricular activities of the Mosque Youth Association include discipline, memorization, grouping and repetition. Meanwhile, the methods used are coaching methods, social activities and direct student involvement. The learning model used is cooperative. The strategies used in extracurricular worship include strategies to get more grades in PAI subjects. Guidance, practice, delivery of prayer material and prayer laws.